Design, production and testing of a micro scale ORC - Bayraktar, Berkhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Energy efficiency and renewable energy technologies are becoming more and more important every day. Organic Rankine Cycle is a proven way of generation of power from low temperature heat sources. In this study a 1 kW Organic Rankine Cycle is designed, produced and tested at BURET Laboratory on Boğaziçi University Sarıtepe Campus. A preliminary thermodynamic analysis is done at MATLAB to select the components. After the selection of the components, the test set-up connections are designed. In order to measure temperature, pressure and flow rate data from the system, a data acquisition system is also designed and programmed. The existing oil heating and chiller systems in BURET laboratory are used as the heat source and heat sink of the system. As the expander, an automobile turbocharger is used. Due to unavailability of very high-speed generators, the compressor of the turbocharger is used to measure the power output. Finally, all of the components are connected, the cycle is built, and testing is done. Due to the unexpected behavior of the pressure sensors, limited data are taken at the most efficient part of the experiment. A maximum turbine power output of 1.55 kW is measured at the turbine output. However, due to the low rotational speed of the turbine, the mechanical power generated by the turbine is not used effectively by the compressor, and a maximum compressor power of 33.15 W is obtained.
Keywords: Energy consumption.; Renewable energy sources.